Rapid detection of Ganoderma-infected oil palms by microwave ergosterol extraction - Md Saad, Muniroh (2015)
Basal stem rot (BSR) is a devastating disease to oil palm in Malaysia. Detection of BSR was based on foliar symptoms and presence of Ganoderma fruiting body. Enzyme-Linked Immunosorbent Assays-Polyclonal Antibody (ELISA-PAB) and Polymerase Chain Reaction (PCR) has been proposed as an early detection method for the disease. However, these techniques are complex, time consuming and have accuracy limitations. In plantations, census needs to be carried out regularly at 6 months interval. Therefore, a robust, rapid and reliable early detection method is highly desirable for large scale BSR monitoring. An ergosterol method was developed, whereby it correlated well with the degree of infection in oil palm. This current study was designed to develop a simpler, rapid and efficient ergosterol detection method with utility in the field using microwave assisted extracted (MAE) method. Pure Ganoderma mycelium (isolated from Gua Musang Felda) was used for optimizing the extraction method with different microwave settings based on microwave power level, temperature and combination of microwave power level and temperature available on the microwave model (Sharp Jet Convectional Grill, model TTAG A437 with capacity 1.5 cu. ft ) with three different exposure time (10, 20 and 30 seconds). The microwave setting with highest ergosterol concentration extracted which is the combination of 70ºC and medium high (MH) power with 30 seconds exposure time was used for the subsequent experiment involving Ganoderma inoculated germinataed oil palm seeds, seedlings and infected field palms for validation of the protocol and also development of semi-quantitative thin layer chromatography (TLC) method. The extraction procedure involves extracting a small amount of Ganoderma mycelium and Ganoderma-infected oil palm stem tissues (0.4g and 1.0g respectively) suspended in low volumes of solvent followed by irradiation in a conventional microwave oven with the best combination of 70°C and MH power for 30 seconds, resulting in simultaneous extraction and saponification. Ergosterol was detected in all infected samples and not detected in healthy samples by thin layer chromatography and high performance liquid chromatography with diode array detection. Healthy samples was describe as palms apparently normal and free from disease compared to infected palms that showed appearance of foliar symptoms and fruiting body at the base of palm trunk or on the trunk of the fallen palm and also at palm stump. The method was particularly effective in extracting high yields of ergosterol (22.65 μg g-1) from infected oil palm and enables rapid analysis of field samples on site allowing infected oil palms to be treated or culled very rapidly. Positive relationship was observed between ergosterol content and inoculation period, where ergosterol concentration increase directly with the increase of inoculation period from day 3 to week 28 (1.04μg g-1 and 28.22μg g-1 respectively) in the inoculated oil palm seedlings. In germinated seeds, ergosterol concentration also increase with the increase in the inoculation period from 6 hours to 168 hours after inoculation ( 0.96 μg g-1 and 8.24 μg g-1 respectively) which means the G. boninense mycelial mass colonizing the roots of the palms also increased. Ergosterol was detected as early as day three after inoculation in diseased oil palm seedlings. These results indicated the early establishment of G. boninense in the root tissues. This present study did not wash or surface sterilizes the roots before extraction of ergosterol, therefore ergosterol can be detected earlier on the root tissues once the fungus attached to the root tissue surface. The result also showed that external disease severity can be observed as early as week eight after inoculation. As disease progresses, palms show a pale appearance, retarded growth and finally death. Besides that, TLC analysis also showed a good correlation with the high performance liquid chromatography (HPLC) quantification where the intensity of the spot produce by TLC analysis showed high intensity of spot for higher ergosterol concentration quantified by HPLC and vice versa. Therefore, a semi-quantitative TLC analysis can be applied for handling large amount of samples during field survey. Based on the present work, it can be concluded that MAE is an efficient method to be used in ergosterol detection where ergosterol acts as biomarker for detection of BSR disease. Besides, TLC analysis can be used for detection of ergosterol in field palms, as it is easier and can be carried out on site and suitable for large field survey during the census.